2010
DOI: 10.1093/neuonc/noq023
|View full text |Cite
|
Sign up to set email alerts
|

Regression of advanced rat and human gliomas by local or systemic treatment with oncolytic parvovirus H-1 in rat models

Abstract: Oncolytic virotherapy is a potential treatment modality under investigation for various malignancies including malignant brain tumors. Unlike some other natural or modified viruses that show oncolytic activity against cerebral neoplasms, the rodent parvovirus H-1 (H-1PV) is completely apathogenic in humans. H-1PV efficiently kills a number of tumor cells without harm to corresponding normal ones. In this study, the concept of H-1PV-based virotherapy of glioma was tested for rat (RG-2 cell-derived) and for huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 27 publications
10
94
0
3
Order By: Relevance
“…The suppressive activity of PVs against various rodent and human cancers has been documented in both in vitro systems and animal models (4,5). PVs distinguish themselves by their dual oncolytic and immunostimulating activities, broad range of target tumors, ability to circumvent tumor cell resistance to conventional death inducers, and suitability for both local and systemic applications.…”
Section: Oncolytic Pvsmentioning
confidence: 99%
See 1 more Smart Citation
“…The suppressive activity of PVs against various rodent and human cancers has been documented in both in vitro systems and animal models (4,5). PVs distinguish themselves by their dual oncolytic and immunostimulating activities, broad range of target tumors, ability to circumvent tumor cell resistance to conventional death inducers, and suitability for both local and systemic applications.…”
Section: Oncolytic Pvsmentioning
confidence: 99%
“…Direct interactions of NS1 with components of the DNA replication (RPA 1-3) and transcription (TBP, TFIIA, and SP1) machineries play a role both in viral DNA replication and transcription and in deregulating DNA/RNA metabolic processes in infected cells [3,4]. Other virus protein-cell protein interactions, such as NS1-CKII [5] and NS2-XPO1 [6], interfere with host cell signaling and nuclear export, respectively. These events affect the host cell dramatically by causing oxidative stress, DNA damage, cell-cycle arrest, cytoskeleton structure rearrangements, mitochondrial membrane depolarization, and/or lysosome permeabilization.…”
Section: Cell Disturbances and Pv Oncolysismentioning
confidence: 99%
“…5 The concept of H-1PV-based virotherapy of glioma was successfully tested in vivo, using rat (RG-2) and human (U87) glioma cell implants in immunocompetent and immunodeficient rat models, respectively. 6 It has to be stated that the therapeutic effect of the virus was more pronounced in immunocompetent animals. Pioneering in vitro studies using a melanoma model have demonstrated that tumor cell killing by a wild-type H-1PV can directly stimulate the maturation of human dendritic cells (DCs) and antigen cross-presentation to cytotoxic T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Although a parallel study with the MVM and H-1 viruses has not being carefully addressed, several subsequent reports suggested that H-1 is a more powerful oncolytic agent against human glioblastoma, regarding the levels of both cytotoxicity and virus yield in culture (Herrero et al 2004;Di Piazza et al 2007). Further recent preclinical studies have convincingly supported H-1 as anti-glioblastoma agent for clinical purposes, as its infection synergized with radiation (Geletneky et al 2010a), and moreover it improved survival and remission of advanced intracranial U87MG human glioblastoma in rat models (Geletneky et al 2010b;Kiprianova et al 2011). However, as discussed below for MVM, there are particularly interesting aspects in the non-productive glioma-parvovirus interaction, as they may uncover molecular processes altered in glioma and helping to identify cellular targets for cancer treatments.…”
Section: Parvoviruses As Oncolytic Agentsmentioning
confidence: 99%